An additively manufactured novel polymer composite heat exchanger for dry cooling applications. (February 2020) - Arie, M.A.; Hymas, D.M.; Singer, F.; Shooshtari, A.H.; Ohadi, M.
Highlights: A first-of-its-kind polymer composite HX was fabricated and experimentally tested. The polymer composite HX was fabricated using a modified FFF 3D printer. Direct transfer of heat between hot and cold fluids by eliminating wall resistance. Much higher heat flow rate per unit mass compared to state-of-the-art technologies. Higher heat flow rate per unit volume compared to state-of-the-art dry technologies. Abstract: The work presented in this paper focuses on the design and thermal characterization of a novel polymer composite heat exchanger (HX) produced by an innovative additive manufacturing process. The heat exchanger represents a gas to liquid configuration in which the gas side removes heat from the liquid side in a cross-flow arrangement. The novel HX utilizes a cross media approach in which, unlike the conventional HXs, the hot and cold sides are directly connected to each other through high conductivity metal fiber fins on the gas side protruding through the walls of the liquid side, thus eliminating the wall resistance separating the hot and cold sides. The HX demonstrates superior thermal performance at reduced pressure drops while also benefiting from the lighter weight and the lower cost that the polymer structure introduces. A 350-W water-to-air heat exchanger was fabricated using a fused filament fabrication (FFF) technique with a novel/patent pending printer head which was developed to produce the metal fiber composite structure of the heat exchanger. The results of the heat exchanger characterization tests show that it yields up to 220% and 125% improvement in heat flow rate over mass ( Q / m ) and heat flow rate over volume ( Q / V ), respectively, when compared to comparable state-of-the-art plate fins HX configurations. This study in particular demonstrates the impact of additive manufacturing in realizing potentially transformative heat exchanger technologies that may otherwise be very difficult to achieve with conventional fabrication methods.